Early developmental stages of a Lower Ordovician marrellid from Morocco suggest simple ontogenetic niche differentiation in early euarthropods - Laibl, Lukáš; Gueriau, Pierre; Saleh, Farid; Pérez-Peris, Francesc; Lustri, Lorenzo; Drage, Harriet B.; Bath Enright, Orla G.; Potin, Gaëtan J.-M.; Daley, Allison C. (Frontiers in Ecology and Evolution, 2023)
Early developmental stages of euarthropods are exceptionally rare in the fossil record. This hampers our understanding of the biology, phylogeny, and development of this extremely diverse metazoan group. Herein, we use classical paleontological methods in combination with synchrotron X-ray microtomography to explore the morphology in ca. 480 million-year-old early developmental stages of the Lower Ordovician Fezouata Shale marrellid euarthropod. These stages range between 3.8 and 5.3 mm in length and are characterized by three distinct pairs of gently curved spines that projects from the head shield. The first pair of cephalic appendages are represented by uniramous antenullae of a sensory function. The second pair of cephalic appendages is robust, and had an anchoring or stabilizing function. The third cephalic appendage pair is composed of long cylindrical podomeres and was used for walking. The trunk appendages are biramous and consist of an endopod and a lamellate exopod. Two anterior trunk endopods are composed of long slender podomeres and were used for walking, while the more posterior trunk endopods bear robust endites and associated setae and were used for food gathering. The trunk of the earliest developmental stages is composed of thirteen segments, in contrast to more than 22 segments in the adult trunk. The similar appendage morphology and differentiation along the body is evident in adult individuals of the Fezouata marrellid, suggesting these different developmental stages shared similar methods of locomotion and food processing. Given that adults and juveniles are often preserved in the same or nearby sites, the niche differentiation between these life stages would be the result of the absolute smaller appendage size in immature stages compared to larger adults, effectively differentiating the size of food resources consumed by each. In addition, the delicate setae present in the posterior trunk appendages of early developmental stages might have been used to capture smaller food particles. This simple mode of ontogenetic niche differentiation might have been common in the early diverging euarthropod groups.